2007
DOI: 10.1126/science.1146757
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Circadian Clock Incorporates a cADPR-Based Feedback Loop

Abstract: Transcriptional feedback loops are a feature of circadian clocks in both animals and plants. We show that the plant circadian clock also incorporates the cytosolic signaling molecule cyclic adenosine diphosphate ribose (cADPR). cADPR modulates the circadian oscillator's transcriptional feedback loops and drives circadian oscillations of Ca2+ release. The effects of antagonists of cADPR signaling, manipulation of cADPR synthesis, and mathematical simulation of the interaction of cADPR with the circadian clock i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
226
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(241 citation statements)
references
References 21 publications
13
226
0
1
Order By: Relevance
“…Moreover Ca 2+ fluxes and ROS production have already been reported to participate in both Cu signalling 54 and circadian rhythm regulation. 55 In light of this, some Cu-regulated categories in our microarray well fit processes that have been previously reported to be circadian clock-regulated: ion homeostasis, osmotic stress responses and cell growth. 56,57 The SDH1-2 expression increased at Cu levels of 5 mM in the growth medium (Fig.…”
Section: Defining Nutritional Cu Ranges At the Molecular Levelsupporting
confidence: 79%
“…Moreover Ca 2+ fluxes and ROS production have already been reported to participate in both Cu signalling 54 and circadian rhythm regulation. 55 In light of this, some Cu-regulated categories in our microarray well fit processes that have been previously reported to be circadian clock-regulated: ion homeostasis, osmotic stress responses and cell growth. 56,57 The SDH1-2 expression increased at Cu levels of 5 mM in the growth medium (Fig.…”
Section: Defining Nutritional Cu Ranges At the Molecular Levelsupporting
confidence: 79%
“…A key piece of molecular-genetic evidence mediating between the plant circadian clock and metabolism was provided by Dodd et al 64 These authors found that cyclic adenosine diphosphate ribose (cADPR), which is synthesized from NAD by the ADP ribosyl cyclase, peaked early in the morning and affected the oscillator. A decrease in the concentration of cADPR lengthened the period of clock-controlled genes, whereas nicotinamide inhibited the ADP ribosyl cyclase and weakened circadian calcium oscillations.…”
Section: Links Between the Plant Circadian Clock And Metabolismmentioning
confidence: 99%
“…A decrease in the concentration of cADPR lengthened the period of clock-controlled genes, whereas nicotinamide inhibited the ADP ribosyl cyclase and weakened circadian calcium oscillations. 64 Previously it was demonstrated that ADPR cyclase activity was induced by ABA and that 30% of all ABA responsive genes were expressed in a similar pattern that those from cADPR. 75 Recalling that circadian clock microarray datasets overlapped with ABA transcriptomic profiles, 63 a link between the circadian clock and metabolism in plants through cADPR has been suggested.…”
Section: Links Between the Plant Circadian Clock And Metabolismmentioning
confidence: 99%
See 2 more Smart Citations